2021
DOI: 10.1109/tmi.2021.3082555
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic-Guided Laparoscopic and Open Hysterectomy Procedures Demonstrated With Human Cadavers

Abstract: Hysterectomy (i.e., surgical removal of the uterus) requires severing the main blood supply to the uterus (i.e., the uterine arteries) while preserving the nearby, often overlapping, ureters. In this paper, we investigate dual-wavelength and audiovisual photoacoustic imaging-based approaches to visualize and differentiate the ureter from the uterine artery and to provide the realtime information needed to avoid accidental ureteral injuries during hysterectomies. Dual-wavelength 690/750 nm photoacoustic imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The gCNR metric has the potential to be incorporated into the design process of photoacoustic imaging systems to resize system components and reduce costs, potentially enabling the proliferation of smaller photoacoustic imaging systems better suited for surgical and interventional suites [13]. Thus, employing gCNR as a prediction tool has the potential to improve the performance of tasks such as tracking catheter tips during cardiac catheterization procedures [18], placing pedicle screws during spinal fusion surgeries [46], visualizing the ureters, uterine arteries, and laparoscopic tool tips during hysterectomies [2], and visual servoing features of interest in a photoacoustic image [12], [18], [47].…”
Section: B Impact Of Proposed Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The gCNR metric has the potential to be incorporated into the design process of photoacoustic imaging systems to resize system components and reduce costs, potentially enabling the proliferation of smaller photoacoustic imaging systems better suited for surgical and interventional suites [13]. Thus, employing gCNR as a prediction tool has the potential to improve the performance of tasks such as tracking catheter tips during cardiac catheterization procedures [18], placing pedicle screws during spinal fusion surgeries [46], visualizing the ureters, uterine arteries, and laparoscopic tool tips during hysterectomies [2], and visual servoing features of interest in a photoacoustic image [12], [18], [47].…”
Section: B Impact Of Proposed Frameworkmentioning
confidence: 99%
“…T HE integration of computer vision with medical imaging is a critical subfield of modern healthcare. Applications of computer vision algorithms in healthcare include classifying disease in medical images [1], segmenting image features of interest to alert surgeons during an operation [2], and tracking targets of interest in robot-assisted procedures [3]- [5], which has the potential to reduce infection rates, shorten hospital stays, and improve postoperative function [6]. These advantages are applicable across multiple medical imaging modalities (e.g., magnetic resonance [7], X-ray [8], ultrasound [9], and photoacoustic [10] imaging), and performance characterization is important for overall system design.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, surgical laparoscopic ultrasound transducers have been employed to delineate biliary anatomy 11,12 or detect hepatic lesions during liver resection. 13 In laparoscopic photoacoustic imaging, new designs have been proposed for various surgical circumstances, such as attachment of diffusing fibers to the laparoscopic ultrasound probe, 14 affixation of a fiber bundle to a laparoscopic grasper tool, 15 or transducer assembly within a laparoscopic housing for photoacoustic nonlinear distortion correction. 16 In each case, the flexible laparoscopic probe contains a rigid acoustic sensor that can be deflected, thus applied pressure is necessary to maintain acoustic coupling contact.…”
Section: Introductionmentioning
confidence: 99%
“…The manipulated fiber also has a limited illumination region in the US field of view, resulting in a small monitoring region. Allard et al later demonstrated a similar PA guidance system by separating the insertion of the US probe and the optical fiber, which was attached to the da Vinci surgical tool 18 , and Wiacek et al performed laparoscopic hysterectomy procedure on a human cadaver to demonstrate the concept 19 . Moradi et al reported a da Vinci-integrated PA tomography with the diffusion optical fiber separately incised into the prostate region through the urethra.…”
Section: Introductionmentioning
confidence: 99%